2006
DOI: 10.1007/bf03061053
|View full text |Cite
|
Sign up to set email alerts
|

Thought suppression, dissociation, and context sensitivity

Abstract: Various studies have found that dissociative experiences, as measured by the Dissociative Experiences Scale (DES), are related to thought suppression, as measured by the White Bear Suppression Inventory (WBSI). The link between dissociation and thought suppression was further investigated in a sample of undergraduate students (n = 220). Firstly, previous research was replicated and extended. More specifically, a robust correlation between DES and WBSI was found, even when more pathological manifestations of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Other samples. Employing a nonclinical sample, Giesbrecht, Merckelbach, and Smeets (2006) provided further evidence for a link between dissociation and poor cognitive inhibition during emotional states (Dorahy et al, 2006). The researchers used an undergraduate sample (N ϭ 40) to investigate thought suppression in response to an emotional video fragment.…”
Section: Emotional Information Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other samples. Employing a nonclinical sample, Giesbrecht, Merckelbach, and Smeets (2006) provided further evidence for a link between dissociation and poor cognitive inhibition during emotional states (Dorahy et al, 2006). The researchers used an undergraduate sample (N ϭ 40) to investigate thought suppression in response to an emotional video fragment.…”
Section: Emotional Information Processingmentioning
confidence: 99%
“…Such an analysis should not only advance our understanding of the etiology of dissociation, but ultimately contribute to the treatment of dissociative disorders. Giesbrecht, Merckelbach, & Smeets (2006) Undergraduates (N ϭ 40) -DES-T related to inferior suppression performance Information-processing task (neutral and threatening stimuli) G. Waller et al (1995) Undergraduates (N ϭ 105) -Levels of dissociation related to slowness identifying the presence of threat words TNT Wessel et al (2005) High DES (Ͼ20) undergraduates (n ϭ 35)…”
Section: Studying Cognitive Processes In the Dissociative Disordersmentioning
confidence: 99%
“…The total WBSI scale score was used in all these studies to measure trait TS, as it was considered to have a single-factor structure. However, other studies have found it to have a two-factor structure composed of a TS factor and another of intrusive thoughts (Giesbrecht et al, 2006;González Rodríguez et al, 2008;Kennedy et al, 2016). Therefore, the results found in those studies could be biased by not considering a two-factor scale structure.…”
Section: Discussionmentioning
confidence: 94%
“…Researchers should continue to explore the relations between dissociation and selective and divided attention and the possibility that failure to attend to multimodal simultaneous stimuli or reduced cognitive flexibility might explain the findings. In addition, future studies could also include alternative tasks to evoke negative emotions, as dissociative traits appear to have more impact during aversive tasks (DePrince & Freyd, 1999; Dorahy et al, 2005; Giesbrecht et al, 2006). The present study also signals the importance of considering mood when exploring the connections between sleep and dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, clinical research reported that individuals with dissociative identity disorder (DID) experienced weakened inhibition and increased negative priming effects in stressful task situations (Dorahy, McCusker, Loewenstein, Colbert, & Mulholland, 2006) and in response to negative words (Dorahy, Middleton, & Irwin, 2005), indicating lower selective attention capacity under stress or negative arousal. In addition, students scoring higher on dissociation showed difficulties suppressing emotional thoughts in response to an emotional video fragment (Giesbrecht, Merckelbach, & Smeets, 2006).…”
mentioning
confidence: 99%